Proceedings of the European Automotive Congress EAEC-ESFA 2015 - Andreescu, Cristian; Clenci, Adrian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The volume includes selected and reviewed papers from the European Automotive Congress held in Bucharest, Romania, in November 2015. Authors are experts from research, industry and universities coming from 14 countries worldwide. The papers are covering the latest developments in fuel economy and environment, automotive safety and comfort, automotive reliability and maintenance, new materials and technologies, traffic and road transport systems, advanced engineering methods and tools, as well as advanced powertrains and hybrid and electric drives.
Keywords: Automotive engineering; Automotive Engineering